MUMPS OUTBREAK RESPONSE IN A PRIMARY SCHOOL IN CONDONGCATUR SLEMAN - Alfi Maziyya, Arifah; Ratu Boelqiah Assaad, Andi; Dharmawidjaja, Isa; Oktaria, Vicka (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: On September 10, 2024, seven primary school students with neck swelling were reported to the Sleman District Health Office (DHO) by Depok II Primary Health Care (PHC). Purpose: This study aimed to confirm and characterize the outbreak and recommend control measures. Methods: A descriptive study was conducted based on person, place, and time. A case was defined as someone who experienced swelling in the cheek or neck area with or without symptoms of fever, sore throat, headache, and no appetite at SDN X from August to September 2024. The population-at- risk (PAR) was defined as people at SDN X in August to September 2024. Data was collected via Google Form and analyzed with graphs and tables. Results: Among 244 PAR, 17 cases were identified (attack rate = 6.96%). The highest attack rate was in class 1A (38.5%, 10/26). Predominant symptoms included swollen cheeks or neck (100%) and fever (88%). The index case was a 7-year-old girl in class 1A, symptomatic from August 28. Cases peaked from September 8-14 (n=7). Case management was carried out by having symptomatic students rest at home until recovery to prevent further transmission. Awareness education on mumps, handwashing, mask use, distancing, and dissemination of guidelines on mumps vigilance were implemented following outbreak confirmation. Conclusions: A mumps outbreak was confirmed at a primary school in Condongcatur, Sleman. The recommendation, schools should monitor for mumps symptoms and report cases to PHC promptly and immediately take actions according to their policies.